Predictive Abilities of Epworth Sleepiness Scale and Stop Bang in Identifying Patients at High Risk of Obstructive Sleep Apnea - Maria Habib, Aimen Hina Khan, Sadia Imtiaz, Jamal Ahmed, Maj. Gen Jawad Khaliq Ansari, Jawed Akbar Dars (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of the study is to evaluate the diagnostic precision of utilizing both Stop-bang and Epworth sleepiness scale in predicting obstructive sleep apnea (OSA) for individuals with clinical suspicion, while considering polysomnography as the reference standard. Methods and Material: A cross-sectional (validation) study was conducted between 4th September 2017 and 3rd January 2018 at the Department of Pulmonology, Military Hospital Rawalpindi. A total of two hundred and eight (n=208) clinically suspected cases of OSA between age 40-60 years irrespective of gender were enrolled in the study. ESS and stop-Bang score was measured in all patients compared with apnea-hypopnea index (AHI). Diagnostic accuracy of combined ESS/Stop-Bang was calculated. Results: The findings of our research indicate that the utilization of combined ESS/Stop Bang (with a cut off point of ESS>3/STOP BANG >10) yielded a sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 73.7%, 66.7%, 79.7%, 58.8% and 71.2% respectively. Conclusion: ESS/Stop-Bang when combined allow diagnosis of OSA with reasonable accuracy. The outcomes of our investigation revealed that the accuracy, sensitivity, specificity, NPV and PPV were 71.2%, 73.7%, 66.7%, 58.8% and 79.7% correspondingly. Keywords: Epworth sleepiness score, Obstructive sleep apnea, Stop-Bang